Status of dhps and dhfr genes of Plasmodium Falciparum in Colombia Before Artemisinin Based Treatment Policy (2012)
ABSTRACT: Introduction: Surveillance of the genetic characteristics of dhps and dhfr can be useful to outline guidelines for application of intermittent preventive therapy in Northwest Colombia and to define the future use of antifolates in artemisinin-based combination therapy schemes. Objective: To evaluate the frequency of mutations in dhps and dhfr and to characterize parasite populations using msp-1, msp-2 and glurp in historic samples before artemisinin-based therapy was implemented in the country. Methods: A controlled clinical study was carried out on randomly selected Plasmodium falciparum infected volunteers of Northwest Colombia (Turbo and Zaragoza). A sample size of 25 subjects per region was calculated. Treatment efficacy to antifolates was assessed. Molecular analyses included P. falciparum genotypes by msp-1, msp-2 and glurp and evaluation of the status of codons 16, 51, 59, 108 and 164 of dhfr and 436, 437, 540, 581 and 613 of dhps. Results: In total 78 subjects were recruited. A maximum number of 4 genotypes were detected by msp-1, msp-2 and glurp. Codons 16, 59 and 164 of the dhfr gene exhibited the wild-type form, while codons 51 and 108 were mutant. In the dhps gene, the mutant 437 glycine was detected in 85% on day 0, while codons 436, 540, 581 and 613 were wild-type. Conclusions: Plasmodium falciparum populations were very homogeneous in this region of Colombia, and the triple mutants of dhfr and dhps Asn108, Ile51 and Gly437 were predominant in clinical isolates